Depression is a predictor for both smoking and quitting intentions among male coronary artery disease patients - Fang-Chun Wei; Chi-Hung Huang; Yen-Ping Tsai; Chii Jeng (Intelektual Pustaka Media Utama, 2023)
Coronary artery disease (CAD) is the third most prominent cause of death globally, and smoking is the most common risk factors for CAD. However, few studies have examined both smoking and smoking cessation intentions in patients with CAD. The study aims to explore the predictors for smoking and quitting intentions among male CAD patients. This was a cross-sectional study. A total of 368 male CAD patients were recruited and classified into never smoked, quit smoking, and continuing to smoke three groups. Demographic information, level of nicotine dependence, carbon monoxide concentration, depression, and resilience were analyzed by using t-test, one- way analysis of variance (ANOVA), and least significant difference (LSD) post-hoc test and the multiple logistic regression analysis. The results revealed that among participants, 23.1% had never smoked, 40.5% had quit smoking, and 36.4% continued to smoke. Multiple logistic regression analysis revealed that age (OR=0.95, 95% CI=0.90–0.99), carbon monoxide (OR=1.74, 95% CI=1.51–2.01), and depression (OR=1.13, 95% CI=1.04–1.23) predicted participants who continued to smoke. Among the 134 participants who continued to smoke, 35.8% exhibited no intention to quit, and 64.2% planned to quit. Nicotine dependence (OR=0.79, 95% CI=0.66–0.94) and depression (OR=1.10, 95% CI=1.02–1.20) were significant predictors in participants who intended to quit smoking. The study demonstrates that depression is a significant predictor for both smoking and quitting intentions among male CAD patients.